Reduction Behavior of CaO–Fe₂O₃–8 wt% SiO₂ System at 1123, 1173 and 1223 K with CO–N₂ Gas Mixtures - Chengyi Ding; Xuewei Lv; Kai Tang; Senwei Xuan; Yun Chen; Jie Qiu (The Minerals, Metals and Materials Society, 2017)
The influence of SiO2 on the reducibility of the CaO–Fe2O3–SiO2 system was fully examined in this study. The isothermal reduction kinetics of CF and CF8S (CaO/Fe2O3 = 1:1, wt% (SiO2) = 8) were investigated through thermogravimetric analysis at 1123, 1173, and 1223 K with 30% CO and 70% N2 gas mixtures. The reduction of the samples with 8% SiO2 was not only highly accelerated but also proceeded easily. Rate analysis revealed that CF and CF8S reduction occurs in two stages, the Fe3O4-to-FeO stage overlaps with the previous Fe2O3-to-Fe3O4 stage and tends to approach the following FeO-to-Fe stage with the addition of SiO2. The apparent activation energy values of CF and CF8S reduction are 46.89 and 8.71 kJ mol−1. Sharp analysis indicated that CF and CF8S reduction was expressed by the Avrami–Erofeev equation presenting a 2D shrinking layer reaction.